Standard Guru Malaysia Dalam Program Persediaan Guru Reka Bentuk Dan Teknologi - Abd Baser, Jamil; Mohd Suhaimi, Nurul Syahada; Othman, Hasyamuddin; Hasan, Azman; Rahim, Mohd Bekri; Nur Yunus, Mohd Faizal Amin (Online Journal for TVET Practitioners, 2017)
Malaysia Teacher’s Standard (MTS) is a guideline towards professionalism competency among teachers that are necessary to achieve by every teachers in Malaysia. MTS contained three standards stated as Standard 1 teacher’s professionalism value practice, Standard 2 knowledge and understanding, as well Standard 3 teaching and learning skill. The purpose of this study is to identify the perception of Design and Technology teachers on the level of teacher’s professionalism value practice standard, level of knowledge and understanding standard also the level of teaching and learning skill standard. Besides, this study also aims to identify the difference of competency level between male and female teachers on MTS level. This descriptive survey is using five Likert scale questionnaires and had been distributed to 155 respondents. The respondents of this study involved students from the Technical and Vocational Education Department (TVED) at Teacher’s Education Institute Campus of Tun Hussein Onn, Batu Pahat and Teacher’s Education Institute Campus of Temenggong Ibrahim, Johor Bharu. The data obtained were analyzed using Software Package for Social Science (SPSS) Version 22.0. The result shows that the overall mean score for teacher’s perception toward professionalism value practice standard level was at high interpretation with mean score of 4.64. Followed by the mean score for teacher’s perception on knowledge and understanding standard level, also teaching and learning skill standard level which both obtained overall mean score of 4.56 and 4.60. The analysis of competency level by Design and Technology teachers based on gender indicates that there is no difference between male and female perception. The findings shows that there are three standard in Malaysia Teacher’s Standard which Standard 1 teacher’s professionalism value practice, Standard 2 knowledge and understanding also Standard 3 teaching and learning skill that need to be applied in teaching training program to produce excellent and competent Design and Technology teacher.